Keefektifan Relaksasi Nafas Dalam Terhadap Penurunan Stres Pada Lansia Di Uptd Pelayanan Sosial Lanjut Usia Tresna Werdha Natar Lampung Selatan - Rahma Elliya; Yopita Sari; Eka Yudha Chrisanto (Universitas Malahayati Lampung, 2021)
ABSTRACT: THE EFFECTIVENESS OF DEEP BREATHING RELAXATION TO ELDERLY REDUCED STRESS IN TRESNA WERDHA ELDERLY NURSING HOME IN NATAR OF SOUTH LAMPUNG DISTRICT IN 2019 Introduction: mental problems that often occur in elderly include stress, anxiety, and depression. The elderly suffered mental problems such as not precious feeling, loneliness, and lost. When these stressing conditions continue and are not mitigated immediately, then they would cause elderly’s mental problems. The survey and observation 17 elderly suffered moderate stress with characteristics including easy to be fatigue, tensed back muscles, losing sleeping time, guilty feeling, fear and anxiety, hard beat chest, and trembling body.Objective: the objective of this research was to find out the effectiveness of deep breathing relaxation to elderly reducedMethod: this was a quantitative and quasi-experiment research by using one group pretest and posttest design. Population was 17 respondents and samples were of total population. Data were analyzed by using dependent t-test by using DASS questionnaires with 14 items as measurement instrument.Result: the average scores of stresses before and after breathing relaxation therapy 2019 were 21.53 and 16.29 respectively. The statistic test result derived p-value 0.000 α 0.05.Conclusion: Ther is aeffectivenessof deep breathing relaxation therapy to elderly reduced. The researcher suggests that the deep breathing relaxation therapy can be used to reduce elderly stress in TresnaWerdha Elderly Nursing Home. This therapy can be used as alternative medication concerning stress to mitigate psychological problems of elderly especially stress. Keywords: Deep Breathing Relaxation, Stress Level ,Elderly INTISARI:KEEFEKTIFAN RELAKSASI NAFAS DALAM TERHADAP PENURUNAN STRES PADA LANSIA Pendahuluan : Masalah mental yang sering terjadi pada lansia adalah stres, kecemasan dan depresi. Lansia yang mengalami masalah mental mulai mengalami perasaan tidak berharga, kesepian dan kehilangan. Apabila kondisi stres ini terus menerus terjadi pada lansia dan tidak di atasi secepatnya maka akan berdampak kemasalah kejiwaan lansia. Hasil Survei dan Observasi didapatkan, 17 lansia dengan stres sedang, ciri-ciri fisik mudah lelah, otot punggung terasa tegang, kehilangan waktu tidur, perasaan bersalah, timbul perasaan ketakutan dan kecemasan, jantung berdebar-debar, serta badan sering gemetar.Tujuan : Diketahui Keefektifan Relaksasi Nafas Dalam Terhadap Penurunan Tingkat Stres Pada Lansia.Metode : Jenis Penelitian Kuantitatif, Rancangan Penelitian Quasi Experimen Design Dengan Pendekatan One Grup Pretes- Posttes Design. Populasi dalam Penelirian ini Sebanyak 17 responden dan Sampel Penelitian ini Menggunakan Total Sampling, Uji statistik menggunakan uji t-tes dependen dan menggunakan alat ukur DASS 14 item.Hasil : Pada penelitian ini sebelum diberikan relaksasi nafas dalam didapat nilai mean 21,53 dan setelah diberikan terapi relaksasi nafas dalam didapat nilai mean 16,29, hasil uji statistik didapatkan nilai p value 0,000 dimana p value α (0,05).Simpulan : Ada Keefektifan Relaksasi Nafas Dalam Terhadap Penurunan Stres Pada Lansia. Saran dari peneliti Teknik relaksasi nafas dalam dapat dijadikan pengobatan alternatif dalam panti khususnya tentang stres serta mampu menanggulangi masalah psikologis lansia terutama masalah stres yang muncu Kata Kunci: Relaksasi Nafas Dalam, Stres, Lansia